Teachers and Students Appraisal of Secondary School as Custodian of Moral Values - Bello Bolanle Muhinat (Universitas Muhammadiyah Makassar, 2021)
Abstract. This study examines how secondary school plays its role as a custodian of moral values in society. What it takes to teach moral values in the school. What are the facilities, subjects, punishments, as well as teaching methods adopted by the school? All these are what the study set out to examine. This was verified using 15 purposively sampled secondary schools in the Sokoto metropolis. The study adopted a descriptive survey design. A questionnaire with psychometrics properties of 0.72 and 0.81 for validity and reliability respectively, was used to elicit the needed data from the respondents which constituted both teachers and students of the selected schools. The findings reveal the current state secondary school Sokoto state lacks in its role to serve as a custodian of moral values, from its facilities, subjects, enforcing conformity, and teaching strategies. In conclusion, for secondary school to perform its role as custodian of moral values, it was recommended among others that there should be the provision of more facilities conducive to teaching and learning in the schools to enable the secondary school plays its role as a custodian of moral values in the society.